PENGARUH FAKTOR PENDAPATAN PEDAGANG, PENDAPATAN SUAMI, UMUR, TINGKAT PENDIDIKAN, DAN JUMLAH TANGGUNGAN KELUARGA TERHADAP CURAHAN JAM KERJA PEDAGANG BUMBON WANITA (Studi Kasus di Pasar Johar Kota Semarang) - Riana, Ade; Sasana, Hadi (Diponegoro Journal of Economics, 2013)
Based on data from the Central Bureau of Statistics (2012), women’s hours of work was more than men in the Semarang City, this condition was not different from women bumbon traders in Pasar Johar. This study aims to analyze the factors that affect hours of work for women bumbon traders in Johar Market, as well as to know the contribution of women bumbon traders income to family income. Sample of women bumbon traders in Pasar Johar was used in this study, as many as 90 respondents from a population of 749. The samples by using a proportional sampling, and the data collected will be analyzed with multiple linear regression model with OLS (Ordinary Least Square) approach. Interviews with the questionnaire method (direct interview) is the technique of execution of this study.The results of this analysis was indicated that income and number of dependents in the family influenced positively to hours of work. Husband's income and education level influenced negatively to hours of work. Women bumbon traders’s income contributed to the family income is quite high, amounting to 52.02 percent.